PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF MATEMATIKA BERBASIS CANVA PADA MATERI CIRI-CIRI BANGUN DATAR MENGGUNAKAN TEORI BRUNER DI SEKOLAH DASAR - M. Ridho Risdian Ma’arip; Putri Eka Fitria AE; Sazkiah Aulia Al Amin; Alfiana Nurussama; Teten Ginanjar Rahayu (STKIP Subang, 2025)
This study aims to develop and test the feasibility and practicality of interactive mathematics learning media based on Canva on the topic of characteristics of flat shapes, grounded in Bruner's learning theory for elementary school students. The study used a Research and Development (R&D) method with the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects were 28 fourth-grade students of SD Negeri 9 Nagrikaler in a limited trial. Data were collected through expert validation sheets and student response questionnaires. The validation results showed a percentage of 92.4% from media experts and 95.1% from material experts, with an average of 93.75% (very valid). The practicality test obtained percentages of 79.26% for the media aspect, 80.81% for the material aspect, and 83.63% for the usefulness aspect, with an average of 81.18% (very practical). Based on these results, the Canva-based interactive mathematics learning media developed is deemed feasible and practical to use in teaching the characteristics of flat shapes in elementary schools. This media is able to support active, contextual learning and is in line with students' thinking characteristics through the application of enactive, iconic, and symbolic stages in Bruner's theory.